20 big trucks in the middle of the street - Lee, Mark; Cyrus, Kurt (Somerville, Mass. : Candlewick Press, 2013)
Count the trucks getting stuck in a traffic jam in this rhythmic read-aloud sure to draw in kids who love everything on wheels.
Keywords: Trucks; Counting; Stories in rhyme; Picture books for children; Fiction; Juvenile works